Efficient and Error-Free Replication past a Minor-Groove N(2)-Guanine Adduct by the Sequential Action of Yeast Rev1 and DNA Polymerase ζ - Washington, M. Todd (American Society for Microbiology, 2004)
Rev1, a member of the Y family of DNA polymerases, functions in lesion bypass together with DNA polymerase ζ (Polζ). Rev1 is a highly specialized enzyme in that it incorporates only a C opposite template G. While Rev1 plays an indispensable structural role in Polζ-dependent lesion bypass, the role of its DNA synthetic activity in lesion bypass has remained unclear. Since interactions of DNA polymerases with the DNA minor groove contribute to the nearly equivalent efficiencies and fidelities of nucleotide incorporation opposite each of the four template bases, here we examine the possibility that unlike other DNA polymerases, Rev1 does not come into close contact with the minor groove of the incipient base pair, and that enables it to incorporate a C opposite the N(2)-adducted guanines in DNA. To test this idea, we examined whether Rev1 could incorporate a C opposite the γ-hydroxy-1,N(2)-propano-2′deoxyguanosine DNA minor-groove adduct, which is formed from the reaction of acrolein with the N(2) of guanine. Acrolein, an α,β-unsaturated aldehyde, is generated in vivo as the end product of lipid peroxidation and from other oxidation reactions. We show here that Rev1 efficiently incorporates a C opposite this adduct from which Polζ subsequently extends, thereby completing the lesion bypass reaction. Based upon these observations, we suggest that an important role of the Rev1 DNA synthetic activity in lesion bypass is to incorporate a C opposite the various N(2)-guanine DNA minor-groove adducts that form in DNA.